Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1089/pho.2012.3263
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Low-Level Laser Versus Low Intensity Pulsed Ultrasound on New Bone Formed Through Distraction Osteogenesis

Abstract: LIPUS and LLLT applied during the distraction period accelerated the DO treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…LIPUS is a safe therapeutic technique that has been successfully used in sports medicine field, primarily for fractured bone healing (Bashardoust Tajali, Houghton, MacDermid, & Grewal, 2012) or distraction osteogenesis (El-Bialy et al, 2002;El-Bialy, Elgazzar, Megahed, & Royston, 2008;Kocyigit et al, 2012;Salem and Schmelz, 2014). In the orthodontic field, LIPUS has also been proven to enhance tooth regeneration in animals undergoing mandibular distraction osteogenesis (El-Bialy, El-Moneim Zaki, & Evans, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS is a safe therapeutic technique that has been successfully used in sports medicine field, primarily for fractured bone healing (Bashardoust Tajali, Houghton, MacDermid, & Grewal, 2012) or distraction osteogenesis (El-Bialy et al, 2002;El-Bialy, Elgazzar, Megahed, & Royston, 2008;Kocyigit et al, 2012;Salem and Schmelz, 2014). In the orthodontic field, LIPUS has also been proven to enhance tooth regeneration in animals undergoing mandibular distraction osteogenesis (El-Bialy, El-Moneim Zaki, & Evans, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of which, 31 studies were eliminated after reviewing the abstracts which clearly showed these papers did not meet the criteria. Of the 19 potentially eligible articles retrieved in full text [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 2 were excluded as they used high intensity ultrasound (2 W/cm 2 ) [27,28] and 2 studies were published in 2 articles each and were thus considered as one study for the purpose of the research [11,12,23,24], leaving 15 eligible studies included in the systematic review (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…All studies used the pulsed technique exclusively, except for one study which compared the pulsed technique with continuous ultrasound treatment [22]. One study compared the effect of lowlevel laser versus LIPUS on rabbit mandible [26].…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, numerous techniques, methods, and materials have been researched to accelerate the maturation of regenerated bone, including hormones, calcium sulphate, growth factors, and electronic and ultrasonic stimulation. 3,4 Osteoblastic cells, which are bone formative, and osteoclastic cells, which are bone resorptive, are both vital to DO. Together, the formation and resorption of bone tissue are known as bone remodelling.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…This process is actualized when osteoblasts and osteoclasts work together physiologically. 1,2,3,4,5 In practice, the bone tissue remodelling mechanism is organized by the activity of systemic hormones (melatonin, oestradiol, parathyroid, and growth hormones), as well as by bone marrow and osteoid matrix-derived growth factors. Of particular interest among these systemic hormones is melatonin, because of its osteoblastic activity.…”
Section: Declaration Of Interestsmentioning
confidence: 99%